Managing the digital transformation change: A case for the Chartered Accountant in South Africa - Nienaber, Mandy (The IIE, 2022)
The South African Institute of Chartered Accountants (SAICA) is South Africa’s pre-eminent accountancy body and widely recognised as one of the world’s leading accounting institutes. These professionals hold positions as leaders in their spheres of business operation. The accelerating advancement of digital technologies is rapidly changing the way businesses operate. This requires Chartered Accountants to transform digitally at a corresponding pace, adopt new methods of doing business, circumnavigate advancing disruptive technologies, prepare for undefined evolving roles, and enhance value creation strategies. This study contains the findings of an examination on the research problem of inadequate speed of adoption of rapidly changing technologies to maintain the relevance of the Chartered Accountant profession in South Africa. The main objective is to develop a change management model that will accelerate digital transformation in the profession. An on-line quantitative survey questionnaire was distributed to all 49 113 Chartered Accountants registered with The South African Institute of Chartered Accountants (SAICA). The survey was distributed via email directly by SAICA to its member database. Employing a sample of 218 Chartered Accountants (SA), quantitative data was obtained and analysed on the impact of digital transformation on the profession, the readiness of the profession, the skills and competencies required and the barriers to adoption. The sample size of 218 CAs is relatively large enough to mitigate against data variability. The findings suggested that disruptive technological advances had significantly impacted the industries and roles of Chartered Accountants. Accountants and auditors had featured in the top five job roles of decreasing demand, highlighting required evolving roles. Only one-third of respondents agreed that the profession locally had adapted quickly enough and a notable 86% of respondents required improved competencies and skills. Disruptive technologies were new to many in the profession, and while most had a basic understanding, very few considered themselves technically proficient or well-experienced. Accountants required new or strengthened essential skills in data management, coding and an understanding of databases and cloud computing. The top three emerging skills were analytical thinking and innovation, critical thinking, and analysis and complex problem-solving. The top three barriers to adoption of innovative technologies by CAs(SA) were an insufficient understanding of opportunities, skills gaps in the local labour market and skills gaps in leadership. Transformation in people, processes and infrastructure is required to enhance value and efficiency. This includes governance, policies and procedures, talent management, employee engagement and information security. Some of the suggested practical change management mechanisms are: • the Honours Degree and the Board Examination curriculum to include a required module on Digital Transformation covering proficiency in artificial intelligence, big data, coding, IT ethics, IT governance and cybersecurity. • SAICA to offer formal SAICA Business School Online accreditation programmes on proficiency in analytical thinking and innovation; critical thinking; and analysis and complex problem-solving; • SAICA’s CPD policies and procedures to include requirements for CAs(SA) to attend at least some of the extensive online CA of the Futures seminars and conferences already offered by SAICA; Findings based on a series of robustness or sensitivity analyses suggest that the empirical results are generally reported to be robust. Based on the study, the slow adoption of digital transformation may be attributed to an insufficient understanding of opportunities, skills gaps in the local labour market and skills gaps in leadership. Empirical results indicate conclusively the inadequate speed of adoption of rapidly changing technologies to maintain the relevance of the Chartered Accountant profession in South Africa. The study appropriately suggests a change management model to accelerate the speed of adoption by CAs(SA) of disruptive technologies and how to manage the change.
Keywords: Change management; Chartered Accountant; Digital transformation; Fourth Industrial Revolution; Innovation; Disruptive technologies